Dynamics of conversational utterances - Alis, Christian M. (National Institute of Physics, College of Science, University of the Philippines Diliman, 2013)
Conversations allow the quick transfer of short bits of information and an utterance is a turn in a conversation. Analysis of conversations usually focus on turn-taking patterns and effects of social structure on conversations. Little is known, therefore, on the dynamics of utterances themselves. Using conversations in works of fiction and in the online social networking platform Twitter, we show that the utterance length of conversations is shortening with time but adapts more strongly to the constraints of the communication medium. This indicates that the introduction of any new medium of communication can affect the way natural language evolves. The shortening of utterances, on the other hand,can be explained by increasing usage of jargon, which in turn, is a possible evidence of segregation of Twitter users into groups, and of faster adoption of new words and word forms.The variability of conversational utterances implies that conversations are not immutable and readily adapt with external factors.